حماية رأس المال في التأمين التكافلي : الشركة الإسلامية اليمنية للتأمين التكافلي نموذجا - عفوري، معاذ مصطفى علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to clarify the meaning of takaful and its legitimacy from the ‎Islamic perspective. In addition, the researcher also aims to explain capital protection ‎methodologies of takaful, as well as to differentiate between capital protection and ‎capital guarantee. Moreover, the research also analyses the capital protection ‎methodology as practiced by the Yemen Islamic Insurance Company in facing various ‎issues related to shareholder and policyholder capital with the objective to suggest ‎Shariah compliant investment. This topic is considered a topic that needs further ‎research because it is related to contemporary Islamic issues. Therefore, the researcher ‎will study the issue from Islamic perspective. To achieve these objectives, the ‎researcher depends on the inductive method to get information from related literature, ‎as well as the analytical method to analyse capital protection methodologies applied by ‎the Yemen Islamic Insurance Company. This will enable the researcher to analyse the ‎financial indicators relating to the performance of Takaful operators, the underwriting ‎process and the surplus of the company. More importantly, it also depends on the field ‎study to obtain required information by conducting interviews with the related officers ‎from the capital protection committee. The research finds that the Yemen Islamic ‎Insurance Company highly relies on contractual capital protection such as mudharabah ‎and wakalah bi al-ajri, as well as qard hasan which is followed by re-takaful. The ‎researcher also suggests a few recommendations at the end of this thesis.